Perceived stress of adolescents during the COVID-19 lockdown: Bayesian multilevel modeling of the Czech HBSC lockdown survey - Furstova, Jana; Kascakova, Natalia; Sigmundova, Dagmar; Zidkova, Radka; Tavel, Peter; Badura, Petr (Frontiers in Psychology, 2022)
Objective: Long-term isolation, including lockdowns and quarantines, may have a distressing effect on anyone experiencing it. Adolescent brain architecture is very sensitive to environmental adversities, and the mental health development of adolescents may be particularly vulnerable during the pandemic era. In order to better understand the triggers for perceived adolescent stress (PSS) during the Covid-19 lockdown, the present study aimed to assess the effects of social well-being and changes in time use during the lockdown, as well as the family Covid experience of adolescents. Methods: The sample for this study comprised n=3,440 adolescents (54.2% girls; mean age=13.5 ± 1.6 years). Bayesian correlations between PSS, health and well-being variables were assessed. PSS was then modeled as an outcome variable in a series of nested Bayesian multilevel regression models. Results: The negative impact of the Covid-19 lockdown was more apparent in girls. PSS was moderately correlated with adolescent health and well-being. The strongest predictor of higher level of PSS was frequent feeling of loneliness. On the contrary, lower level of PSS was most associated with having someone to talk to. Conclusions: Long-term social isolation of adolescents could be harmful to their mental health. Psychological coping strategies to prevent the consequences of social isolation and development of mental health problems should be promoted on the individual, family, and even community level.